Juvenile dermatomyositis at a tertiary care hospital: is there any change in the last decade?. (26th October 2013) - Prasad, Shiva; Misra, Ramnath; Agarwal, Vikas; Lawrence, Able; Aggarwal, Amita
Abstract: Introduction: Juvenile dermatomyositis (JDM) is a rare multisystem disorder of childhood primarily involving the skeletal muscles and skin. Patients and methods: The case records of patients with JDM seen at our centre in the last 10 years were reviewed and data on clinical presentation, management, outcome and complications were retrieved. Results: Eighteen patients (nine boys) were diagnosed as JDM with median age at presentation of 12.5 years, duration of illness of 9.25 months and follow‐up duration of 24 months. At presentation, rash was seen in all patients, 17 had muscle weakness, fever in 11 and arthritis in six. Gottron's lesions and heliotrope rash were seen in 14 and 11 patients, respectively. Calcinosis was seen in five patients and lipoatrophy in two patients. Four patients had dysphagia, one each had dilated cardiomyopathy and respiratory failure. Electromyograph was abnormal in 15 patients and antinuclear antibodies were positive in nine patients. Prednisolone and methotrexate were used in 17 patients. Other disease‐modifying anti‐rheumatic drugs used were hydroxychloroquine, azathioprine, cyclophosphamide and cyclosporine. Sixteen patients achieved remission. Five patients had pyogenic infections and one patient died of this. In addition two patients had tuberculosis. Conclusion: Compared to our experience in the previous decade we saw more girls, used methotrexate upfront but the median duration of illness and prevalence of calcinosis (30%) was the same, suggesting that we need to improve awareness about JDM among paediatricians for early referral.